Eosinophilic myocarditis - Webb Webb, Kembly María (2020)
Eosinophilic myocarditis (EM) was first described in 1936 by Wilhelm Loeffler. This pathology presents an infiltration of eosinophils in myocardium, with hypereosinophilia  association or not, with several etiologies described, and even cases of unknown cause. The clinical presentation of this pathology can be a little symptomatic, until presenting heart failure or death, can also develop restrictive cardiomyopathy by fibrosis. The definitive diagnosis is made by endomyocardial biopsy, where the histology shows infiltrates of eosinophils and necrosis of myocytes. The most used treatment in this pathology are corticosteroids with good results in most cases.